2020
DOI: 10.21203/rs.3.rs-43770/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioinformatic Analysis Revealing Mitotic Spindle Assembly regulated NDC80 and MAD2L1 as Prognostic Biomarkers in Non-Small Cell Lung Cancer Development

Abstract: Background Lung cancer has been the leading cause of tumor related death, and 80%~85% of it is non-small cell lung cancer (NSCLC). Even with the rising molecular targeted therapies, for example EGFR, ROS1 and ALK, the treatment is still challenging. The study is to identify credible responsible genes during the development of NSCLC using bioinformatic analysis, developing new prognostic biomarkers and potential gene targets to the disease. Methods Firstly, three genes expression profiles GSE44077, GSE18842 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…After analyzing clinical samples, the experimental model was utilized to search for further support. We found that knockdown of MAD2L1 signi cantly decreased proliferation and promoted apoptosis of ES cells in vitro and in vivo, in line with previous reports that MAD2L1 acts as an oncogene in various cancers, including gastric cancer, rhabdomyosarcoma, and colorectal cancer [25,29,30]. Xia et al revealed that MAD2L1 promotes the proliferation and migration of rhabdomyosarcoma cells [14].…”
Section: Discussionsupporting
confidence: 90%
“…After analyzing clinical samples, the experimental model was utilized to search for further support. We found that knockdown of MAD2L1 signi cantly decreased proliferation and promoted apoptosis of ES cells in vitro and in vivo, in line with previous reports that MAD2L1 acts as an oncogene in various cancers, including gastric cancer, rhabdomyosarcoma, and colorectal cancer [25,29,30]. Xia et al revealed that MAD2L1 promotes the proliferation and migration of rhabdomyosarcoma cells [14].…”
Section: Discussionsupporting
confidence: 90%
“…GEO database has been one of the most commonly used public databases for worldwide researchers to explore the genetic abnormalities in various cancers [ 36 – 39 ]. In the study, we firstly picked four different cDNA expression profiles GSE53757, GSE53000, GSE71963 and GSE68417 from GEO database to analyze the differently expressed genes in ccRCC comparing to normal renal tissue, and the result revealed 192 genes that were shared in four profiles including 39 up-regulated and 153 down-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…GEO and TCGA database have been two most commonly used public databases for worldwide researchers to explore the genetic abnormalities in various cancers [36][37][38][39]. In the study, four different cDNA expression pro les GSE53757, GSE53000, GSE71963 and GSE68417 were picked from GEO database based on their sample number for further analyzing the differently expressed genes in ccRCC comparing to normal renal tissue, and the result revealed 192 genes that were shared in four pro les including 39 up-regulated and 153 down-regulated genes.…”
Section: Discussionmentioning
confidence: 99%